Human Rights Education: A Review - Tiwari, Dr. Chandrani (International Journal of Multidisciplinary Research Configuration, 2024)
Today Education is one of the most important functions of the government. It is required for the performance of our most basic responsibilities. It is the principal instrument in awakening the human beings to culture values, non-judgementalism, and tolerance and in preparing them to adjust to complex environments where rights and duties cooperate. Human Right Organization aim to protect human right education on different levels, some being more specific to geographical areas, others are based on governmental influences, others are non profit and education based, some are mainly aimed to protect a certain group of individuals. Several schools offer human rights education as a part of their curriculum like the linked subjects like history, Politics and citizenship but there are also specialized courses, such as Human Rights offered as part of the International Baccalaureate Diploma programme for high school studies.